The Application of Lysinibacillus sphaericus for Surface Treatment and Crack Healing in Mortar - Farrugia, Christine; Borg, Ruben Paul; Ferrara, Liberato; Buhagiar, Joseph (Frontiers in Built Environment, 2019)
Micro-cracks, which develop during the service life of reinforced concrete structures, reduce the durability of concrete through the penetration of fluids. Microbially-induced calcium carbonate precipitation (MICP) occurs naturally in the presence of ureolytic bacteria which precipitate calcium carbonate (CaCO3) through urea hydrolysis. This deposition leads to the filling of micro-cracks and sealing of pores, reducing ingress of fluids into the concrete. The research aims were to assess the potential of Lysinibacillus sphaericus for healing cracks in concrete and to study the effects of this treatment on the absorption properties of treated concrete. Lysinibacillus sphaericus was cultivated in vitro and induction of MICP through urea hydrolysis was tested on cement paste with two different calcium sources. The calcium precipitates where characterised by light microscopy, Scanning Electron Microscopy, Energy Dispersive Spectroscopy and Fourier Transform Infrared Spectroscopy. The final phase of the study involved testing of the crack healing capacity and the effect on absorption of the MICP process on mortar samples. These parameters were measured by means of visual examinations, light & digital microscopy, Ultrasonic Pulse Velocity (UPV) and absorption tests. The study confirmed that MICP is induced successfully on concrete using Lysinibacillus sphaericus. Samples exposed to repeated treatment cycles of Lysinibacillus sphaericus in the presence of a calcium source, exhibited a more extensive and even coating of CaCO3 crystals on the surface confirming that repeated cycles of treatment are more effective in increasing the amount of CaCO3 deposition and therefore increasing crack healing capacity. Digital microscopy and UPV analysis proved that this precipitate was successful in partially healing cracks in samples. Sorptivity tests confirmed this and showed that it was also successful as a surface treatment to reduce absorption.